Inhibitory effects of Sanguisorba officinalis root extract on HYBID (KIAA1199)‐mediated hyaluronan degradation and skin wrinkling. (9th January 2019) - Yoshida, H.; Yamazaki, K.; Komiya, A.; Aoki, M.; Kasamatsu, S.; Murata, T.; Sayo, T.; Cilek, M. Z.; Okada, Y.; Takahashi, Y.
Abstract: Objectives: Hyaluronan (HA), an important constituent of extracellular matrix in the skin, has many biological activities such as hydration that contributes to firmness and bounciness of the skin. We have reported that reduction in HA in the papillary dermis and over‐expression of HYBID (HYaluronan Binding protein Involved in hyaluronan Depolymerization, alias KIAA1199 or CEMIP), a key molecule for HA degradation in skin fibroblasts, are implicated in facial skin wrinkling in Japanese and Caucasian women. However, little or no information is available for substances which inhibit the HYBID‐mediated HA degradation. Methods: Inhibition of Sanguisorba officinalis root extract and ziyuglycoside I, one of the components of Sanguisorba officinalis root extract, to the HYBID‐mediated HA degradation was assessed by size‐exclusion chromatography of HA depolymerized by stable transfectants of HYBID in HEK293 cells (HYBID/HEK293 cells) or normal human skin fibroblasts (Detroit 551 cells and NHDF‐Ad cells). The HYBID mRNA and protein expression was examined by quantitative real‐time PCR and immunoblotting in the skin fibroblasts treated with Sanguisorba officinalis root extract, and size distribution of newly produced HA was evaluated by preparing metabolically radiolabelled HA. A double‐blind, randomized and placebo‐controlled study was carried out in the 21 healthy Japanese women, who were topically treated with the formulation containing Sanguisorba officinalis root extract or the placebo on each side of the face including crow's foot area. Results: Sanguisorba officinalis root extract, but not ziyuglycoside I, abolished HYBID‐mediated HA degradation by HYBID/HEK293 cells. Sanguisorba officinalis root extract also inhibited HYBID‐mediated HA degradation in skin fibroblasts by down‐regulating HYBID mRNA and protein expression. Although control untreated skin fibroblasts produced polydispersed HA, the cells treated with Sanguisorba officinalis root extract produced only high‐molecular‐weight HA. Treatment with Sanguisorba officinalis root extract‐formulated lotion significantly improved skin elasticity, and reduced skin wrinkling scores at the outer eye corner compared with the placebo formulation. Conclusion: Sanguisorba officinalis root extract showed an anti‐HYBID‐mediated HA degradation activity and anti‐wrinkle activity on human facial skin, which is accompanied by the improvement in elasticity. Our study provides the possibility of a new strategy to inhibit HYBID‐mediated HA degradation for anti‐wrinkle care.